HAMBATAN MEMPEROLEH SERTIFIKASI HALAL PERSPEKTIF PELAKU UMKM DI DESA BANDAR KLIPPA - Astia, Mirza; Yusnita; Sijabat, Abygael Paulina (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2025)
Halal certificate is not only valid proof that the product produced is safe and in accordance with the provisions of Islamic law, but also plays an important role in increasing the competitiveness of micro, small and medium enterprises (UMKM) in the domestic and global markets. This research generally aims to determine the obstacles to UMKM in Bandar Klippa Village in obtaining halal certification. The type of research used in this research is a qualitative method with collection through field research and literature research. The results obtained from this research are external obstacles, namely uneven socialization and education from the government, expensive processing costs and complicated and long administrative procedures. The internal obstacles faced by Bandar Klippa Village UMKM actors in obtaining halal certification are limited resources, lack of halal knowledge and awareness and the perception of UMKM actors that halal certification is not urgently needed.